2021
DOI: 10.3390/su13031359
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ethical Leadership on Employees’ Innovative Behavior: The Role of Organization-Based Self-Esteem and Flexible Human Resource Management

Abstract: Employees’ innovative behavior is a vital source for promoting the sustainable survival and development of enterprises. Innovation is a complicated and high-risk mental process, where in each stage employees’ innovative attitude and behavior will be affected by the varying behaviors of their direct leaders. Therefore, exploring the intricate relationship between leadership behavior and employees’ innovative behavior is necessary. Based on social exchange theory, this study builds a cross-level moderation model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 49 publications
4
42
0
3
Order By: Relevance
“…The innovative behavior intervention that employees were willing to adopt in their undertakings leads to enhanced job performance. This is parallel to the study conducted by (Wen et al, 2021;Vitapamoorthy et al, 2021;Natorina, 2019;Suryani et al, 2019;van Zyl et al, 2019).…”
Section: Conclusion and Managerial Implicationssupporting
confidence: 77%
See 1 more Smart Citation
“…The innovative behavior intervention that employees were willing to adopt in their undertakings leads to enhanced job performance. This is parallel to the study conducted by (Wen et al, 2021;Vitapamoorthy et al, 2021;Natorina, 2019;Suryani et al, 2019;van Zyl et al, 2019).…”
Section: Conclusion and Managerial Implicationssupporting
confidence: 77%
“…The study on the mediating effect of innovative behaviour is still at the infancy stages. According to (Wen et al, 2021;Vitapamoorthy et al, 2021;Bos-Nehles et al, 2017;Ali & Buang, 2011), the study on the impact of innovative behaviour and as an intervening factor has been the aim of many scholars, and it is still in its early stages. Besides, innovative behaviour is crucial for the sustainable development of online retailers, which leads to better employee and organisational performance according to (Natorina, 2019;Baird, 2018;Parviainen et al, 2017).…”
Section: The Mediating Role Of Innovative Behaviour Between Self-efficacy and Job Performancementioning
confidence: 99%
“…Self-esteem represents the self-concept of individuals, which plays a vital role in the lives of everyone, affecting psychological, physical well-being, enthusiasm, and life satisfaction (Cameron and Granger, 2019). In addition, earlier studies revealed that OBSE engenders many positive outcomes, i.e., stress management (Costantini et al, 2019), individual performance (Hahn and Mathews, 2018) and organizational citizenship behaviors (Kim and Beehr, 2018a), and innovative behaviors (Ali, 2021;Wen et al, 2021). Moreover, OBSE reduces uncertainty (Neves et al, 2020), as individuals having OBSE can handle stressful situations effectively (Costantini et al, 2019).…”
Section: Organization-based Self-esteem As Mediatormentioning
confidence: 99%
“…Human resource management practices describe the management methods that enable firms to obtain valuable and outstanding information, as well as impact creative activity and greater performance ( Cao et al, 2021 ). HRM impacts workers’ job-related attitudes, talents, and behaviors in order to achieve an organization’s goals, and it plays a crucial role in creating an atmosphere that is conducive to knowledge management and innovation ( Wen et al, 2021 ). Because knowledge and innovation have origins in human psychology, numerous previous studies have recommended adopting HRM strategies to better encourage the development and dissemination of knowledge for improved organizational innovation performance ( Than et al, 2021 ).…”
Section: Theoretical Underpinning and Hypothesis Developmentmentioning
confidence: 99%